Engaging senior high school students in online listening instruction - Abdul Kodir Al-Baekani (ELT in Focus, 2023)
Listening is the most important skill for language learning because it is the most used language skill in normal daily life. Obviously in communicating or learning something begins with listening. Learning listening using song media in high school has indeed been applied, but some students need something new, creative, and not boring. Therefore, there is one appropriate learning media named Lyricstraining.com. This media is one of the innovation of teacher. The objective of this research is to find out the perception of one of senior high school students in Indonesia about the use of Lyricstraining.com learning media in listening activity. This research was qualitative research. Data was collected for 15 students through an open-ended questionnaire. Each student has given the questionnaire. The participants is a students at senior high school in Karawang. The result show that students has a positive perception of the use lyricstraining.com website. They perceived that: 1). Lyricstraining makes learning listening effective, 2). Lyricstraining helps increasing students listening skill and vocabulary, and 3) Lyricstraining makes learning listening more fun and enjoy. The finding also found several other perceptions from using Lyricstraining.com to support their learning activities, such as: Lyricstraining can train focus and easy to use for beginners.